2021
DOI: 10.1093/nop/npab020
|View full text |Cite
|
Sign up to set email alerts
|

Defining and timing of palliative opportunities in children with central nervous system tumors

Abstract: Background Children with brain and central nervous system (CNS) tumors experience substantial challenges to their quality of life during their disease course. These challenges are opportunities for increased subspecialty palliative care (PC) involvement. Palliative opportunities have been defined in the pediatric oncology population, but the frequency, timing, and factors associated with palliative opportunities in pediatric patients with CNS tumors are unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In PPC; an ethically sensitive EOL decision that is frequently made is withholding/withdrawing LST in situations where LST is no longer deemed to be meaningful or effective [13]. Hospital-wide audits of paediatric deaths [14][15][16][17] and retrospective studies in paediatric intensive care units (PICUs) [18,19] revealed that a significant factor associated with children's deaths is the medical decision to withhold/withdraw LST.…”
Section: Introductionmentioning
confidence: 99%
“…In PPC; an ethically sensitive EOL decision that is frequently made is withholding/withdrawing LST in situations where LST is no longer deemed to be meaningful or effective [13]. Hospital-wide audits of paediatric deaths [14][15][16][17] and retrospective studies in paediatric intensive care units (PICUs) [18,19] revealed that a significant factor associated with children's deaths is the medical decision to withhold/withdraw LST.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative opportunities have been previously defined 29–31 . A priori, nine palliative opportunities were defined, including disease progression/relapse, hematopoietic stem cell transplantation (HSCT) or chimeric antigen receptor T‐cell (CAR‐T) therapy, phase 1 trial enrollment, admission for severe symptoms, social concerns, EOL care, intensive care unit (ICU) admission, DNR status, and hospice enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…29 Previous studies have evaluated palliative opportunities in specific disease populations: bone and soft tissue sarcomas, leukemia/lymphoma (LL), and central nervous system (CNS) tumors. [29][30][31] The primary aim of this study was to provide a framework to explore and understand a patient's disease course not by diagnosistreatment-relapse-death, but in terms of palliative opportunities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations